Association Study Confirmed Three Breast Cancer‐Specific Molecular Subtype‐Associated Susceptibility Loci in Chinese Han Women. (13th April 2017) - Xu, Yihui; Chen, Mengyun; Liu, Chenchen; Zhang, Xiaowei; Li, Wei; Cheng, Huaidong; Zhu, Jun; Zhang, Mingjun; Chen, Zhendong; Zhang, Bo
Abstract : Background: Breast cancer is a heterogeneous and polygenic disease that can be divided into different molecular subtypes based on histological and genomic features. To date, numerous susceptibility loci of breast cancer have been discovered by genome‐wide association studies and may expand the genetic features. However, few loci have been further studied according to molecular subtypes. Materials and Methods: We genotyped 23 recently discovered single nucleotide polymorphisms using the Sequenom iPLEX platform in a female Chinese cohort of 3, 036 breast cancer patients (2, 935 samples matched molecular subtypes) and 3, 036 healthy controls. Results: Through a stratification analysis, 5q11.2/MAP3K1 (rs16886034, rs16886364, rs16886397, rs1017226, rs16886448) and 7q32.3/LINC-PINT (rs4593472) were associated with Luminal A, and 10q26.1/FGFR2 (rs35054928) was associated with Luminal B. Conclusion: In our study, breast cancer‐specific molecular subtype‐associated susceptibility loci were confirmed in Chinese Han women, which contributes to a better genetic understanding of breast cancer in different molecular subtypes. Abstract : Genome‐wide association studies have identified many susceptibility loci associated with breast cancer. The aim of this study was to further analyze according to molecular subtype, leading to validation of breast cancer‐specific molecular subtype‐associated susceptibility loci in Chinese Han women.